GEOQUÍMICA DO SEDIMENTO DO PANTANAL BRASILEIRO - REMOR, MARCELO BEVILACQUA (2016)
Floodplains have a high potential for nutrients transformation, however, when they accumulate at critical levels, generates an ecosystem degradation. The hydrological regime that controls nutrient dynamics in floodplains it is very responsive to changes in soil use and soil occupation or by changes climate pattern. In this context, this research aimed at reconstructing the history of nutrient accumulation and eutrophication of the Brazilian Pantanal, identifying the factors and/or phenomena that have influenced those variables. The sedimentation cores were collect in ponds that showed permanent connections to the main channel of Paraguai, São Lourenço and Cuiabá Rivers. The sediment cores were sliced in two-centimeter uniform intervals and quantification of total organic carbon and total nitrogen were carried out by readings in CNS elemental analyzer. Quantification of phosphorus was carried out by mass spectroscopy by inductively coupled plasma. The organic carbon in sediment of Brazilian Pantanal is mainly from allochthonous origin, being the nitrogen and phosphorus nutrients limiting of the productivity in the system, elements whose origins are agricultural practices in the drainage basin. The establishment of geochemical background is indispensable to determine the actual state of soils and sediments contamination. However, there is no scientific consensus about the methodology to determine those values. In this sense, this paper has established the geochemical background in Brazilian Pantanal sediments, based on the integrated method, in order to identify the appropriate calculation methodology for that region. The use of integrated methods, mainly the non-parametric statistics, has proved be useful in reliably determining geochemical reference values. Therefore, the authors recommend integrated methods to establish the geochemical background for others points in the Brazilian Pantanal.